Arthroscopic Osteochondral Grafting for Radiocarpal Joint Defects - Ho, Pak-cheong; Tse, Wing-Iim; Wong, Clar Wing-Yee; Chow, Esther Ching-San (Journal of Wrist Surgery, 2013)
Background Focal chondral lesion is a common cause of chronic wrist pain. The best treatment remains unknown. We have developed a technique of arthroscopic transplantation of an osteochondral autograft from the knee joint to the distal radius with satisfactory clinical results.Materials and Methods Between December 2006 and December 2010, four patients (average age 31 years) with posttraumatic osteochondral lesions over the dorsal lunate fossa were treated with arthroscopic osteochondral grafting. Pre- and postoperative motion, grip strength, wrist functional performance score, pain score, and return to work status were charted. Postoperative computed tomography (CT) scan, magnetic resonance imaging (MRI), and second-look arthroscopy were performed to assess graft incorporation.Description of Technique With the arthroscope in the 3–4 portal, synovitis over the dorsal lunate fossa was débrided to uncover the underlying osteochondral lesion. We employed the 6-mm trephine of the Osteoarticular Transfer System (OATS) to remove the osteochondral defect. Osteochondral graft was harvested from the lateral femoral condyle and delivered into the wrist joint arthroscopically.Results In all cases, grafts incorporation was completed by 3–4 months postoperative. All patients showed improvement in the wrist performance score (preoperative 27.5, postoperative 39 out of 40) with no pain on final follow-up at average 48.5 months (range 24–68 months). Grip strength improved from 62.6 to 98.2% of the contralateral side. Motion improved from 115.5 to 131.3°. X-ray images showed preserved joint space. Patient satisfaction was high with no complication.Conclusion An arthroscopic-assisted transfer of an osteochondral graft is a viable treatment option for chondral defects of the distal radius.
Keywords: wrist arthroscopy; osteochondral graft; radiocarpal joint; wrist surgery; focal; osteochondral defect